Ecosystem function in predator–prey food webs—confronting dynamic models with empirical data. Issue 2 (7th September 2018) - Curtsdotter, Alva; Banks, H. Thomas; Banks, John E.; Jonsson, Mattias; Jonsson, Tomas; Laubmeier, Amanda N.; Traugott, Michael; Bommarco, Riccardo
Abstract: Most ecosystem functions and related services involve species interactions across trophic levels, for example, pollination and biological pest control. Despite this, our understanding of ecosystem function in multitrophic communities is poor, and research has been limited to either manipulation in small communities or statistical descriptions in larger ones. Recent advances in food web ecology may allow us to overcome the trade‐off between mechanistic insight and ecological realism. Molecular tools now simplify the detection of feeding interactions, and trait‐based approaches allow the application of dynamic food web models to real ecosystems. We performed the first test of an allometric food web model's ability to replicate temporally nonaggregated abundance data from the field and to provide mechanistic insight into the function of predation. We aimed to reproduce and explore the drivers of the population dynamics of the aphid herbivore Rhopalosiphum padi observed in ten Swedish barley fields. We used a dynamic food web model, taking observed interactions and abundances of predators and alternative prey as input data, allowing us to examine the role of predation in aphid population control. The inverse problem methods were used for simultaneous model fit optimization and model parameterization. The model captured >70% of the variation in aphid abundance in five of ten fields, supporting the model‐embodied hypothesis that body size can be an important determinant of predation in the arthropod community. We further demonstrate how in‐depth model analysis can disentangle the likely drivers of function, such as the community's abundance and trait composition. Analysing the variability in model performance revealed knowledge gaps, such as the source of episodic aphid mortality, and general method development needs that, if addressed, would further increase model success and enable stronger inference about ecosystem function. The results demonstrate that confronting dynamic food web models with abundance data from the field is a viable approach to evaluate ecological theory and to aid our understanding of function in real ecosystems. However, to realize the full potential of food web models, in ecosystem function research and beyond, trait‐based parameterization must be refined and extended to include more traits than body size. Abstract : Dynamic food web models could aid our understanding of ecosystem functions driven by trophic interactions, but are rarely tested against data. The authors confront a trait‐based food web model with field data, and show that it can explain observed abundance dynamics of an arthropod herbivore and provide insight into ecosystem functioning.